2011
DOI: 10.1074/jbc.m110.204933
|View full text |Cite
|
Sign up to set email alerts
|

Critical Roles of Interactions among Switch I-preceding Residues and between Switch II and Its Neighboring α-Helix in Conformational Dynamics of the GTP-bound Ras Family Small GTPases

Abstract: GTP-bound forms of Ras family small GTPases

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 31 publications
1
14
1
Order By: Relevance
“…S6C). 31 P NMR measurements indicate that mutations that disrupt hydrogen bonds along this network alter interactions between H-Ras and the GTP-analogue (36). In addition, mutations of H-Ras paralogs that abut or are located on helix 3 (Arg68Thr, Asp69Asn, Met72Ile, Asp92Asn, Asp92Tyr, Arg97Gly) have been identified in cancers (37), supporting the idea that the network is critical for the function of H-Ras (Fig.…”
Section: Discussionmentioning
confidence: 55%
“…S6C). 31 P NMR measurements indicate that mutations that disrupt hydrogen bonds along this network alter interactions between H-Ras and the GTP-analogue (36). In addition, mutations of H-Ras paralogs that abut or are located on helix 3 (Arg68Thr, Asp69Asn, Met72Ile, Asp92Asn, Asp92Tyr, Arg97Gly) have been identified in cancers (37), supporting the idea that the network is critical for the function of H-Ras (Fig.…”
Section: Discussionmentioning
confidence: 55%
“…We suggest that the differences in dynamic changes observed for EF-Tu AV-165/314 and EF-Tu AV-47/314 versus EF-Tu AV-33/315 result from differential mutation and labeling effects on the dynamic equilibrium between the EF-Tu structural extremes. All three EF-Tu mutants in this study have mutations positioned spatially close either to switch I (positions 33 and 47) or to helix C (position 165) and, in the related protein, ras p21, mutations in the corresponding regions are known to affect the balance between two GTP-bound conformations ( 43 , 44 ). Similarly, a mutation in the switch II region causes the EF-Tu·GDP complex to adopt an ‘EF-Tu·GTP’-like behaviour ( 45 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was revealed that state 1 assumes an open structure distinguishable from state 2 by the loss of the direct and Mg 2+ -coordinated indirect hydrogen-bonding interactions of Thr-35 in switch I with the c-phosphate of GppNHp, which causes marked deviation away from the guanine nucleotide and conformational instability of the switch I loop [6]. Further analyses showed the importance of the Gly-60-c-phosphate direct hydrogen-bonding interaction and the switch II-a3-helix interaction in stabilizing the state 2 conformation [6,10]. In particular, H-RasT35S-GppNHp yielded two distinct state 1 crystal structures, form 1 and form 2, showing the existence of polysterism in switch I and switch II [6].…”
Section: Introductionmentioning
confidence: 99%